Freshwater crabs from the D. R. Congo, Central Africa: A new species of Arcopotamonautes Bott, 1955, and a redescription of A. stappersi (Balss, 1936) (Brachyura: Potamoidea: Potamonautidae) - Cumberlidge, Neil; Hildreth, Rachael B.; Craig, Delphia (Zootaxa, 2026)
A new species of freshwater crab from the Democratic Republic of the Congo, Central Africa is described based on previously unidentified museum material. Potamon (Potamonautes) johnstoni stappersi Balss, 1936, also from the D. R. Congo, is here recognized as a valid species and redescribed following examination of the type material and other specimens from Tanzania. The new taxa are assigned to Arcopotamonautes Bott, 1955, based on a combination of characters of the carapace, chelipeds, mouthparts, and gonopods. These species are compared to, and distinguished from, similar Arcopotamonautes species found in Central and East Africa. Illustrations and a distribution map are provided.